The actor's workbook : a practical guide to training, rehearsing and devising + video - Clifton, Alex (New York : Bloomsbury Methuen Drama, 2016)
'The Acting Workbook is an essential workbook for actors, actors in training and teachers of acting and drama. The workbook and video provide a clear, step-by-step guide to learning techniques in acting. The book presents a system of exercises which will develop core acting skills, offers techniques for developing an authored role and models for devising new work. These techniques are based on the practices of Konstantin Stanislavski and his recent theatrical descendants including Uta Hagen, Sanford Meisner, Michael Chekhov and others. The exercises in the book are outlined in a student-centred approach, offering not only in-class exercises, but also pre-class exercises, educational frameworks, teaching-tips, suggested texts through which to apply the work, follow-up exercises and suggestions for further reading in each chapter. Enabling and guiding the actor's sustainable, communicable, believable transformation into an imagined reality, this workbook is filled with powerful and precise acting tools, each underpinned by a rigorous and well-explained philosophy of practice. The Acting Workbook includes video of the author teaching the exercises, with professional actors demonstrating the techniques to be learned'--
Machine generated contents note: A beginning -- Part One: Play -- Chapter One. Release -- Chapter Two. Imagine -- Chapter Three. Listen -- Chapter Four. Pulse -- Chapter Five. Impulse -- Part Two: Inhabit -- Chapter One. Mapping a world -- Chapter Two. Mapping a role -- Chapter Three. Rehearsing a role -- Part Three: Devise -- Chapter One. Deconstruct -- Chapter Two. Construct -- An ending.
Includes index.
Keywords: Acting -- Handbooks, manuals, etc